The results of seabird survey in Pangpang Bay, East Java, Indonesia - Siddiq, Arif Mohammad; Sulistiyowati, Hari; Wimbaningrum, Retno; Setiawan, Rendy; Ananda, Rizky Putra; Qisti, Nissaul (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.